Politicization, depoliticization and policy change: a comparative theoretical perspective on agri-food policy - Feindt, Peter Henning; Schwindenhammer, Sandra; Tosun, Jale (Journal of comparative policy analysis, 2020)
This article introduces a multidimensional concept of (de)politicization, comprising strategy, process and outcome, in order to set the stage for a theoretical model that connects (de)politicization to policy change. The politicization/depoliticization- policy change (PDPC) model facilitates hypothesizing the relationship between different types and degrees of (de)politicization and likely types and degrees of policy change. To demonstrate the merit of the PDPC model for comparative policy analysis, the article discusses dynamics of politicization, depoliticization and policy change in the agri-food domain as an instructive policy area. Finally, the article synthesizes the findings from the contributions to this special issue.
Gesehen am 25.02.2021